OPTIMASI GOOGLE CLASSROOM SEBAGAI INOVASI PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Susilo, Purnomo Hadi; Rohman, M. Ghofar (Universitas Nusantara PGRI Kediri, 2021)
The Covid-19 pandemic has plagued all corners of the world, including Indonesia. Simultaneously, the Ministry of Education and Culture (SE No. 36962/MPK.A/HK/2020), responded that learning during the pandemic can be carried out with an online or remote system and work from home. The application of online learning is a form of innovation that can be done to condition the teaching and learning process in the hope of preventing the spread of the Covid-19 outbreak. One of the online learning applications that can be used to support the learning process during the Covid-19 pandemic is Google Classroom. This Google Classroom application is equipped with classroom features that can be created by educators and can be followed by all students. The features provided are complete, including uploading materials, videos, assignments/practices, and even discussion forums. Research data was taken by distributing online questionnaires using google form to 122 students. These students are those who have done online learning using Google classroom. The results showed that the optimization of the use of Google Classroom can be used to develop online learning with high results, which is 73.57%.